Efficacy of Edible Coating on Refrigerated Storage of Tomatoes - Alam, Md. Shafiq; Singh, Sarpreet (Journal of Agricultural Engineering, 2004)
An experiment was conducted to study the effect of edible coating brand "Taza" on shelf-life and quality of tomatoes stored under refrigerated conditions. Three formulations (0.5, 0.75%, 1.0%) of coatings were tried and applied by immersion method. The quality of stored tomatoes were evaluated on the basis of Physiological weight loss, firmness, total soluble solids, ascorbic acidity, lycopene content and decay % at regular intervals. On the basis of experimental results and statistical analysis, it was observed that 1.0% taza coated tomatoes recorded minimum changes in the quality parameters as compared to 0.5 and 0.75% taza coated tomatoes, thus extending the shelf-life upto 28 days without adversely affecting the quality.